Complete Genome Assemblies of All Xanthomonas translucens Pathotype Strains Reveal Three Genetically Distinct Clades - Goettelmann, Florian; Roman-Reyna, Veronica; Cunnac, Sébastien; Jacobs, Jonathan M.; Bragard, Claude; Studer, Bruno; Koebnik, Ralf; Kölliker, Roland (Frontiers in Microbiology, 2022)
The Xanthomonas translucens species comprises phytopathogenic bacteria that can cause serious damage to cereals and to forage grasses. So far, genomic resources for X. translucens were limited, which hindered further understanding of the host-pathogen interactions at the molecular level and the development of disease-resistant cultivars. To this end, we complemented the available complete genome sequence of the X. translucens pv. translucens pathotype strain DSM 18974 by sequencing the genomes of all the other X. translucens pathotype strains using PacBio long-read technology and assembled complete genome sequences. Phylogeny based on average nucleotide identity revealed three distinct clades within the species, which we propose to classify as clades Xt-I, Xt-II and Xt-III. In addition to 2,181 core X. translucens genes, a total of 190, 588 and 168 genes were found to be exclusive to each clade, respectively. Moreover, 29 non-TALE and 21 TALE type III effector classes were found, and clade- or strain-specific effectors were identified. Further investigation of these genes could help to identify genes that are critically involved in pathogenicity and/or host adaptation, setting the grounds for the development of new resistant cultivars.